Management of Ileosigmoid Knotting: A Literature Review - Atamanalp, Sabri Selcuk; Peksöz, Rıfat; Dişçi, Esra; Atamanalp, Refik Selim; Tatar Atamanalp, Cansu (European Journal of Therapeutics, 2024)
Ileosigmoid knotting (ISK) is a rare double-segment intestinal obstruction form. Urgent surgery is the unique solution in the management of ISK. In surgical treatment, detorsion alone is generally used in patients with viable bowel, while cases with gangrenous bowel require resection. ISK recurrence is uncommon. However, due to the recurrence risk of sigmoid volvulus, the role of recurrence-reducing procedures is unclear. In this review, urgent treatment of ISK as well as the techniques and patient selection criteria of recurrence-reducing management are discussed.